Ask Questions, Get Answers


Solve the equation : $\;-x^{2}+x-2=0\;$

$(a)\;\large\frac{-1 \pm \sqrt{7} i}{-3}\qquad(b)\;\large\frac{-1 \pm \sqrt{3} i}{-2}\qquad(c)\;\large\frac{-1 \pm \sqrt{5} i}{-2}\qquad(d)\;\large\frac{-1 \pm \sqrt{7} i}{-2}$

1 Answer

Answer : $\;\large\frac{-1 \pm \sqrt{7} i}{-2}$
Explanation :
The given quadratic equation is $\;-x^2+x-2=0$
On comparing the given equation with $\;ax^2 + bx +c\;,$ we obtain
$a=-1\;,b=1\;and \;c=-2$
Therefore , the discriminant of the given equation is
$D = b^2 -4ac=1^{2} - 4 \times (-1) \times (-2) =-7$
Therefore , the required solutions are
$\large\frac{-b \pm D}{2a} = -\large\frac{-1 \pm \sqrt{-7}}{2 \times (-1)}$
$=\large\frac{-1 \pm \sqrt{7} i}{-2}\;.$
answered Apr 11, 2014 by yamini.v